Getting to Know Products and Online Marketing Business Actors in Desa Labuan - Tri Wahyudi; Arif Alfian; Irfan Dwi Nurcahya; Naufal Dzaky Irawan; Anggadita Tri Firdaus; Bagas Febriansyah; Elisabeth Marbun; Retno Dwi Rizkiana; Novanka Ramadhanti; Hary Yunisa; Siti Padia Hijriyana; Tiara Junita; Euis Rahmawati; Anggi Ardini; Dine Ayu Fachrunnisa; Tiara Rahmi; Alya Rihhadatul Aisy; Eltia Hernaeni Milatia; Ahmad Salman Alfarisi; Vitaloka Dwi Maharani; Muhammad Hafizh Mubarak; Siti Rohayati (MOVE: Journal of Community Service and Engagement, 2022)
Knowing the product and product marketing is an important part of a trading business. Desa Labuan with the majority of the population as traders needs to know the importance of knowing products and doing marketing, especially online marketing. The implementation of this activity is carried out with the stages of survey, socialization, presentation of survey results and discussion and mentoring. The result of this activity is that business actors are introduced to products and their marketing as well as the importance of making the uniqueness of a product so that it creates enthusiasm for consumers and so that business actors can survive in the existing market competition.